PELATIHAN DAN PENDAMPINGAN PENYUSUNAN PROPOSAL PENELITIAN TINDAKAN KELAS (PTK) BAGI GURU MA AL HUDA WAJAK KABUPATEN MALANG - Siti Sumarsilah; Anita Kurnia Rachman; Susandi Susandi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2021)
Classroom Action Research (CAR) is one of the studies that teachers must make. This research is one proof of teacher professionalism. This Classroom Action Research (CAR) aims to assist teachers in solving problems experienced when teaching and learning activities in the classroom. The activity of preparing a classroom action research proposal was one of the community service activities carried out by the Lecturer of the Indonesian Language and Literature Study Program in collaboration with MA AL Huda Wajak Malang Regency. This service activity originated from the problems faced by partners, namely the teacher did not understand the importance of classroom action research and the techniques for preparing classroom action research proposals. This service activity was carried out for three days with a schedule of activities on the first day of providing material about Classroom Action Research and Classroom Action Research Proposal Formulation. The second and third day carried out activities through the proposal clinic. This activity was attended by Mr. and Mrs. MA AL teacher Huda Wajak. Proposal writing activities through proposal clinics can help teachers understand classroom action research and the preparation of classroom action research proposals.